Charge and energy flows in ionised thymidine. (July 2015) - Maclot, S; Delaunay, R; Piekarski, D G; Domaracka, A; Huber, B A; Adoui, L; Martin, F; Alcamf, M; Avaldi, L; Bolognesi, P; Diaz-Tendero, S; Rousseau, P
Synopsis: We present a combined experimental and theoretical study of the ionisation and fragmentation of the nucleoside thymidine in the gas phase. Two sources of ionisation/excitation are used, namely UV photons and low-energy multiply charged ions, associated with coincidences measurements, respectively photoelec- tron/photofragment (PEPICO) and fragment/fragment. Coupling these experiments with quantum chemistry calculations, we obtain a complete picture of the fragmentation dynamics, in particular the charge and energy transfers within the molecular edifice.